Mulheres em situação de abrigamento : uma abordagem a partir da interseção em uma casa-abrigo - Fonseca, Ericka Evelyn Pereira Ferreira (2015)
The present study analyzes women´s shelter home functioning under using the main public policies to face domestic and family violence against women. In the last years, especially with the Maria da Penha law advent, the domestic violence against women issues has left the private space and entered the public one. In order to resolve the problem, a series of public policies were created, principally to this work, in the matters of women´s shelters home. After effectuated an inventory in the main domestic and family violence public policies, the women´s shelter home will be address in the light of national shelter policy. We also distinguish home shelter and sheltering, as well as analyze a women´s shelter home operation in Aracaju´s city, on Sergipe´s state.This work has four chapters. On the first one, the debate will be set around the main violence against women discussion aspects: the legislation and the public policies created to deal with the problem. On the legislative front, the main focus will be the Maria da Penha Law and the role that legal discourse has in the violence against women context. On the second chapter, we are going to analyze the shelter home as women´s protections public policies. The third chapter will handle the work methodological aspects, bringing the road traveled by the author during the field insertion and the transference and the countertransference involved. Regarding methodology, will be transposed into fieldwork Freud´s recommendations to doctors who were willing to work with psychoanalysis. The last chapter examine shelter home functioning from women´s interviewed account and theoretical references chosen, as Foucault and Goffman. The construction of this work will included the official shelter´s home documents analysis, literature review and interviews collected by the author in contact with institution employees and officers, and especially, in the listening of the women in sheltering situation. The research was produce over that insertion´s experience and analyzed the difference between the normative, provided by official documents, and the factual, the concrete reality of the shelter running, perceived from the researcher´s insertion and women´s reports. Although it´s undeniable the women´s shelter importance in extreme violence contexts, the interviews signal that it can also be a place that produces invisibility and compliance one these women, that so far are defined and regulated in accordance with institutional rules not always welcoming. That way, we analyze not only how women´s representation are built in this shelter home, but also how their subjectively are absorbed by the institution. The scenario shows the need to expand shelter´s policies, by creating others alternatives to the women´s shelter home placement. At the same time, opens the discussion about the importance of improving women´s safe network, which can avoid the shelter itself or at least greatly reduce its incidence.